Tricyclic mappings: revisited - Taoufik, Sabar (Fixed point theory and algorithms for sciences and engineering, 2025)
In order to study the existence of best proximity points of a ( T ) condition satisfying mapping, we introduce a new interesting notion of triangular projection in geodesic metric spaces. Using the famous Schauder fixed point theorem, we obtain a best proximity point result for such mappings.